1935
DOI: 10.1113/expphysiol.1935.sp000666
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ovarian Extracts on the Oxygen Consumption of the Uterus

Abstract: IN a previous paper [1934] the authors have shown that the oxygen consumption rate of the isolated uterus of the rat and mouse shows a cyclical variation. This rate is approximately constant during cestrus and the early part of dicestrus, but it is approximately doubled during the latter part of dicestrus. In the case of ovariectomised animals, however, the rate shows no cyclical variation and is approximately equal to the rate in normal animals during cestrus and early dicestrus. This absence of cyclical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1940
1940
1956
1956

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Positive findings have been reported by Adler & Lipschütz [1922], Neuschloss [1924], Ahlgren [1925], Reinwein & Singer [1928], Ebina [1932], Euler [1932,1933], Verebély [1932], Paal [1933], Davis, Da Costa & Hastings [1934], Mansfeld [1935], Scott [1935], Davis & Hastings [1936] and Haarmann [1936]. On the other hand, Ellinger [1922], Fleischmann [1927], Anselmino et al [1929], Paasch & Reinwein [1929], Rothschild [1930], Horn [1930], Hopping [1930], Myhrman [1932], Hicks [1932], Verebély [1932], Canzanelli & Rapport [1937] and Canzanelli et al [1939] have reported negative results.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Positive findings have been reported by Adler & Lipschütz [1922], Neuschloss [1924], Ahlgren [1925], Reinwein & Singer [1928], Ebina [1932], Euler [1932,1933], Verebély [1932], Paal [1933], Davis, Da Costa & Hastings [1934], Mansfeld [1935], Scott [1935], Davis & Hastings [1936] and Haarmann [1936]. On the other hand, Ellinger [1922], Fleischmann [1927], Anselmino et al [1929], Paasch & Reinwein [1929], Rothschild [1930], Horn [1930], Hopping [1930], Myhrman [1932], Hicks [1932], Verebély [1932], Canzanelli & Rapport [1937] and Canzanelli et al [1939] have reported negative results.…”
supporting
confidence: 60%
“…Foster [1926] observed that thyroidectomy produced a diminished O2 uptake of muscle tissue respiring in glucose, a result also reported by Dye & Maughan [1929a, b] with and without the addition of succinate to the respiring muscle mince. Many workers have reported increases in O2 uptake of surviving tissues after treating animals with thyroxine or thyroid preparations; notably Dresel [1928] in kidney and liver, Anselmino, Eichler & Schlossmann [1929] in liver, spleen and kidney, Hopping [1930] in alligator red blood cells, Hicks [1932] in muscle, McEachern [1932] in heart, Dye [1933] in muscle, Gerard & McIntyre [1933] in liver, auricle and vagus nerve, Meyer, McTiernan & Aub [1933] in liver, Ebina [1932] in liver and kidney, McEachern [1935] in kidney, liver and muscle, Khayyal & Scott [1935] in uterus and Victor & Andersen [1938] in liver and kidney. As far as is known, the only work on the respiration of brain tissue following thyroid treatment is that of Cohen & Gerard [1937].…”
mentioning
confidence: 99%